Nematode diversity in rice fields of Java, Indonesia - FITRIANINGRUM KURNIAWATI; SUPRAMANA SUPRAMANA; R. YAYI MUNARA KUSUMAH; DHIVA SYAFA QUAMILLA; SOBIKHIN SOBIKHIN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Kurniawati F, Supramana, Kusumah RYM, Quamilla DS, Sobikhin. 2025. Nematode diversity in rice fields of Java, Indonesia. Biodiversitas 26: 6273-6284. Rice (Oryza sativa) is a staple crop in Indonesia; however, its productivity is constrained by plant-parasitic nematodes that cause substantial yield losses. This study investigates the diversity and abundance of nematodes in soil and rice roots across Java Island. Soil and root samples were purposively selected based on symptoms of nematode infection, and nematodes were extracted and identified morphologically. Ecological indicators, including Maturity Index family and diversity metrics (H’, E, D), were quantified to evaluate food web structure and soil ecosystem conditions using Microsoft Excel and the NINJA platform. Plant-parasitic nematodes were widely distributed, with Hirschmanniella and Meloidogyne dominating the assemblage, reflecting strong herbivory pressure in flooded rice systems. Free-living nematodes were predominantly bacterivores, indicating a bacterial-driven decomposition pathway typical of anaerobic paddy soils. Maturity Index (MI) values (2.65-3.07) suggested moderate and relatively uniform disturbance across regions, although ΣMI varied significantly, with higher values in Bogor and Malang indicating more mature soil food webs. Diversity indices showed that Malang and Sukabumi exhibited the highest ecological stability, whereas Banten and Bojonegoro displayed low diversity and high dominance, characteristic of stressed environments. The consistently high Enrichment Index (EI) and Structure Index (SI) values indicated active nutrient cycling and resilient trophic structures. Overall, Java’s rice ecosystems experience moderate disturbance yet maintain functionally robust nematode communities, underscoring the need for region-specific management, particularly in high-Plant Parasitic Index (PPI) areas, to improve soil health and mitigate nematode-associated yield losses.